9+(2x+5)=3(2x+4)

Simple and best practice solution for 9+(2x+5)=3(2x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9+(2x+5)=3(2x+4) equation:


Simplifying
9 + (2x + 5) = 3(2x + 4)

Reorder the terms:
9 + (5 + 2x) = 3(2x + 4)

Remove parenthesis around (5 + 2x)
9 + 5 + 2x = 3(2x + 4)

Combine like terms: 9 + 5 = 14
14 + 2x = 3(2x + 4)

Reorder the terms:
14 + 2x = 3(4 + 2x)
14 + 2x = (4 * 3 + 2x * 3)
14 + 2x = (12 + 6x)

Solving
14 + 2x = 12 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
14 + 2x + -6x = 12 + 6x + -6x

Combine like terms: 2x + -6x = -4x
14 + -4x = 12 + 6x + -6x

Combine like terms: 6x + -6x = 0
14 + -4x = 12 + 0
14 + -4x = 12

Add '-14' to each side of the equation.
14 + -14 + -4x = 12 + -14

Combine like terms: 14 + -14 = 0
0 + -4x = 12 + -14
-4x = 12 + -14

Combine like terms: 12 + -14 = -2
-4x = -2

Divide each side by '-4'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| 1.2+0.3x=0.5x-3.2 | | -9x^4=-48x^2+64 | | 0.5x-2+5= | | 14-7r=6-3r | | 19-3x=5x+3 | | 1x-2=-1 | | 2x-2=3x-1 | | 16x-10=6x+40 | | 5.4x-1=4.4x+9 | | (7/6)x+7=4 | | 16x+27=15x+18 | | 40-6x=4x | | 160+x=60 | | 7x+3(x+2)=-24 | | 8x+4y=254 | | 10x^2-(5/6)x-25=0 | | 9x+7=8x-8 | | 6x+27=11x+7 | | 2x^2-7x-39=0 | | 7x+11=11x+7 | | 7x+11=6x+27 | | 50=7x-6 | | 2(2-4x)=10-x | | 9-(2x+5)=3(2x+4) | | 8=x-13 | | x^3+14x=123 | | (4*4)+(r*r)=(r*r)*2*2 | | (4u^2)3/2 | | 3x+12=6x+3 | | m/-3+8=5 | | -24+3r=9 | | -24+3r=99 |

Equations solver categories